The Wehrmacht and National Socialist Military Thinking. (July 2017) - Stahel, David
This article argues that Nazi ideology had a profound impact upon the German officer corps in the Second World War not just for their well-established complicity in criminal activity, but also in their approach to warfare. This article demonstrates that Nazi ideology radicalized pre-existing notions of the German military ethos and conceptions of war, leading to an often irrational world view in which impractical, and even impossible, military undertakings could be 'rationally' explained, accepted, and understood. At the same time, seventy years after the war, a National Socialist influence upon German military thinking has seldom been discussed in the proliferation of Anglo-American operational histories.